2000
DOI: 10.1007/s002130000456
|View full text |Cite
|
Sign up to set email alerts
|

Ventral pallidal extracellular fluid levels of dopamine, serotonin, gamma amino butyric acid, and glutamate during cocaine self-administration in rats

Abstract: These data support a potential role for DA and 5-HT innervations of the VP in intravenous cocaine self-administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…The present pharmacological and neurochemical analyses support the A 2A -induced antagonistic modulation of striatal DA-ergic neurotransmission via the antagonistic A 2A -D 2 receptor-receptor interactions at the plasma membrane level and their indirect interactions at the level of the intra-cellular signaling cascades Trifilieff et al 2011;Borroto-Escuela et al 2013). This interaction inter alia occurs in the ventral striato-pallidal GABA pathway ) which executes expression of rewarding/motivational/seeking properties of cocaine or food (Di Chiara 1995;Sizemore et al 2000;Tang et al 2005;Wydra et al 2013). The enhancing actions of cocaine on D 2 receptor signaling involve also indirect DA releasing actions and direct effects on D 2 receptor signaling in D 2 homo or heteroreceptor complexes like the A 2A -D 2 heteroreceptor complexes Filip et al 2012;Fuxe et al 2013) which leads to enhancement of D 2 -mediated DA neurotransmission.…”
Section: Discussionmentioning
confidence: 96%
“…The present pharmacological and neurochemical analyses support the A 2A -induced antagonistic modulation of striatal DA-ergic neurotransmission via the antagonistic A 2A -D 2 receptor-receptor interactions at the plasma membrane level and their indirect interactions at the level of the intra-cellular signaling cascades Trifilieff et al 2011;Borroto-Escuela et al 2013). This interaction inter alia occurs in the ventral striato-pallidal GABA pathway ) which executes expression of rewarding/motivational/seeking properties of cocaine or food (Di Chiara 1995;Sizemore et al 2000;Tang et al 2005;Wydra et al 2013). The enhancing actions of cocaine on D 2 receptor signaling involve also indirect DA releasing actions and direct effects on D 2 receptor signaling in D 2 homo or heteroreceptor complexes like the A 2A -D 2 heteroreceptor complexes Filip et al 2012;Fuxe et al 2013) which leads to enhancement of D 2 -mediated DA neurotransmission.…”
Section: Discussionmentioning
confidence: 96%
“…However, rats self-administering i.v. cocaine (Sizemore et al, 2000) or receiving acute oral alcohol (Cowen et al, 1998), showed no change in VP GABA release.…”
Section: Gabamentioning
confidence: 87%
“…With regard to the relationship between accumbal dopamine and animal models of drug reward, however, there is evidence that other mesolimbic brain areas may play even more important roles in mediating the rewarding properties of COC. For example, several very recent studies suggest that the ventral pallidum, one of the major output areas of the nucleus accumbens (for review, see Watson et al 1989), is crucial in COC reward (Gong et al 1996(Gong et al , 1997Sizemore et al 2000). Plenty of evidence exists, however, for the relevance of the nucleus accumbens in COC reward; 6-OHDA lesions in the nucleus accumbens are shown to attenuate COC selfadministration (Roberts et al 1977;Pettit et al 1984) and microinjections of COC directly in the shell region of the nucleus accumbens support self-administration (Carlezon et al 1995;McKinzie et al 1999; but see Goeders and Smith 1983).…”
Section: Discussionmentioning
confidence: 99%